Equality of opportunity and student support schemes. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2007)
A positive link between investment in education and labour income has received much attention in the early literature such as Mincer (1958) and Becker (1962). It is a known fact that education particularly higher education plays an important role in promoting intergenerational mobility and economic equality as such that it is considered a tool for redistributional policy.